Education and Empowerment Service Program at Halfway Houses in the Special Region of Yogyakarta - Septiarti, Serafin Wisni; Sugito, S; Setiana, Dafid Slamet; Hakim, Septian Rahman; Booribon, Gumpanat (Studies in Learning and Teaching, 2025)
This research focuses on developing a prototype model of education and empowerment services at halfway houses with the aims of: 1) to produce a prototype model of education and empowerment services that is feasible and practical for use in the management of halfway; 2) to determine the feasibility of the service model; and 3) to determine the practicality of the education and empowerment service model. The research method used is R&D which refers to the Borg & Gall development procedure consisting of problem definition, initial information gathering, planning, initial development, expert validation, revision, initial field trial, continuous revision, full implementation, and evaluation. The validation test subjects were carried out through expert judgement by media/prototype experts and community empowerment experts. The subjects of the product practicality trial were 12 shelter managers. Data collection techniques using validation instruments and product practicality questionnaires. The data that has been obtained is analyzed quantitatively and qualitatively. The assessment results were analyzed by calculating the average ideal score and ideal standard deviation. The results of this study are: 1) producing a prototype model of education and empowerment services at halfway houses through the input, process, and termination stages; 2) the prototype model produced is feasible to use with a very good feasibility category; 3) the prototype model produced is practical to use with a very practical category. Through efforts to improve the management model of the halfway house, it is hoped that it can optimize its role as the spearhead of handling street children.